Mandibular adenomatoid odontogenic tumor: Radiographic and pathologic correlation - More, Chandramani B. (Medknow Publications & Media Pvt Ltd, 2013)
Adenomatoid odontogenic tumor (AOT) is a rare tumor of epithelial origin comprising 3% of all the odontogenic tumors. It is a benign, painless, noninvasive, and slow-growing lesion, with a relative frequency of 2.2-13% and often misdiagnosed as an odontogenic cyst on clinical examination. AOT affects young individuals with a female predominance, occurs mainly in the second decade, and usually surrounds the crown of unerupted teeth. This lesion is most commonly located in the anterior maxilla and rarely in the mandible. It is usually associated with an impacted canine. AOT frequently resembles lesions like dentigerous cyst or ameloblastoma. AOT has three variants, follicular, extrafollicular, and peripheral. The intraoral periapical radiograph is the best radiograph to show radiopacities in AOT as discrete foci having a flocculent pattern within radiolucency even with minimal calcified deposits. These calcified deposits are seen in approximately 78% of the lesions. Herewith, we present the report of four unusual cases of AOT located in the mandible, with an emphasis on radiographic findings and on pathologic correlation, and on reviewing the existing literature on this tumor.